2005
DOI: 10.1002/qua.20537
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of electronic and vibrational properties of neutral, cationic, and anionic B24 clusters

Abstract: ABSTRACT:The equilibrium geometries, electronic and vibrational properties, and static polarizability of B 24 , B 24 Ϫ , and B 24 ϩ clusters are reported here. First-principles calculations based on density functional theory predict the staggered double-ring configuration to be the ground state for B 24 , B 24 Ϫ , and B 24 ϩ , in contrast to the quasi-planar structure observed in small neutral and ionized B n clusters with n Յ 15. Furthermore, the (4 ϫ B 6 ) tubular structure is found to be relatively stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…The flat {1212} sheet has a 6-fold coordination of boron atoms, which is uniformly repeated in a basic triangular three-atom unit. In fact, this terminology can be derived through a planar projection of Aufbau principle 4 where the motifs consisting of a pentagonal pyramidal B 6 and the hexagonal pyramidal B 7 are found to be the basic unit to form elemental boron clusters. The calculated cohesive energy of the flat {1212} sheet is 5.48 eV/atom, higher than that of the sp 2 -bonded hexagonal graphene-like boron sheet, which is only 4.96 eV/atom (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The flat {1212} sheet has a 6-fold coordination of boron atoms, which is uniformly repeated in a basic triangular three-atom unit. In fact, this terminology can be derived through a planar projection of Aufbau principle 4 where the motifs consisting of a pentagonal pyramidal B 6 and the hexagonal pyramidal B 7 are found to be the basic unit to form elemental boron clusters. The calculated cohesive energy of the flat {1212} sheet is 5.48 eV/atom, higher than that of the sp 2 -bonded hexagonal graphene-like boron sheet, which is only 4.96 eV/atom (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Boron holds a unique place among the elements of the periodic table by having the most varied polymorphism, which includes quasicrystal [1] and novel nanostructures [2][3][4][5][6], in addition to the complex icosahedral networks observed in conventional boron-rich solids [7]. Based on a generalization of the Euler-Poincaré formula for a cylinder [8], it was suggested that boron nanotubes (BNTs) could be constructed by the appropriate ÔwrappingÕ of an ÔidealizedÕ triangular boron sheet, referred to as the {1 2 1 2} sheet.…”
mentioning
confidence: 99%
“…a double-ring BNT fragment) with diameter $0.52 nm, can be found in (10,0) zigzag BNT, which is constructed from either the {1 2 2 1} or the {1 2 1 2} boron sheet. On the other hand, the basic unit of the most stable (6,0) zigzag type-I BNT considered in this study, with diameter $0.40 nm, can be found in B 24 [5].…”
mentioning
confidence: 99%
“…Such idea is mainly based on the fact that the DRT configuration is the most stable structure among various isomers of B 20 , B 24 , B 30 , B 36 , and B 96 clusters. [20][21][22][23] Moreover, the DRT clusters have been detected in experiments. 25 Our previous study also showed that for large sized boron clusters the three-ring tubular and DRT configuration are more stable than other ones.…”
mentioning
confidence: 91%